Electromagnetic Shielding of Monolayer MXene Assemblies. Issue 9 (23rd January 2020) - Yun, Taeyeong; Kim, Hyerim; Iqbal, Aamir; Cho, Yong Soo; Lee, Gang San; Kim, Myung‐Ki; Kim, Seon Joon; Kim, Daesin; Gogotsi, Yury; Kim, Sang Ouk; Koo, Chong Min
Abstract: Miniaturization of electronics demands electromagnetic interference (EMI) shielding of nanoscale dimension. The authors report a systematic exploration of EMI shielding behavior of 2D Ti3 C2 T x MXene assembled films over a broad range of film thicknesses, monolayer by monolayer. Theoretical models are used to explain the shielding mechanism below skin depth, where multiple reflection becomes significant, along with the surface reflection and bulk absorption of electromagnetic radiation. While a monolayer assembled film offers ≈20% shielding of electromagnetic waves, a 24‐layer film of ≈55 nm thickness demonstrates 99% shielding (20 dB), revealing an extraordinarily large absolute shielding effectiveness (3.89 × 10 6 dB cm 2 g −1 ). This remarkable performance of nanometer‐thin solution processable MXene proposes a paradigm shift in shielding of lightweight, portable, and compact next‐generation electronic devices. Abstract : Self‐assembly of monolayer MXene and systematic exploration of the electromagnetic interference shielding behavior of 2D Ti3 C2 T x MXene are presented. Theoretical models explain the shielding mechanism below skin depth. A monolayer assembled MXene film (2.3 nm) and 24‐layer film (≈55 nm) offer ≈20% and 99% shielding, respectively. The extraordinarily large absolute shielding effectiveness reaches 3.89 × 10 6 dB cm 2 g −1 .